Isoleucine-to-methionine substitution at residue 148 variant of PNPLA3 gene and metabolic outcomes in gestational diabetes. Issue 2 (17th December 2014) - Bo, Simona; Gambino, Roberto; Menato, Guido; Canil, Stefania; Ponzo, Valentina; Pinach, Silvia; Durazzo, Marilena; Ghigo, Ezio; Cassader, Maurizio; Musso, Giovanni
ABSTRACT: Background: A single nucleotide polymorphism (SNP) of the patatin-like phospholipase-3 ( PNPLA3 )/adiponutrin gene (rs738409 C>G) is strongly associated with nonalcoholic fatty liver disease; to our knowledge, no data are available on the impact of this PNPLA3 SNP on liver and metabolic outcomes during pregnancy in patients with gestational diabetes (GD). Objective: We evaluated the impact of the PNPLA3 rs738409 SNP on liver enzymes, metabolic indexes, and maternal and neonatal outcomes in 200 GD patients enrolled in a lifestyle intervention. Design: In a randomized trial with a 2 × 2 factorial design, exercise significantly improved maternal and neonatal outcomes in GD patients. Effects of the G allele on metabolic and liver indexes and maternal and neonatal outcomes were evaluated in these patients. Results: At the end of the trial, fasting insulin and homeostasis model assessment of insulin resistance (HOMA-IR) values were significantly lower and liver enzymes significantly higher in PNPLA3 G-allele carriers. In a multiple regression model, the G allele was associated directly with aspartate aminotransferase (β = 2.60; 95% CI: 0.99, 4.20), alanine aminotransferase (β = 3.70; 95% CI: 1.78, 5.62), and γ-glutamyl transferase (β = 3.70; 95% CI: 0.80, 6.60) and inversely with insulin (β = −2.01; 95% CI: −3.24, −0.78) and HOMA-IR (β = −0.39; −0.64, −0.14) values at the end of the trial. In a multiple logistic regression model, the G allele was associated directly with risk of developing liver enzyme elevation during pregnancy (OR: 4.21; 95% CI: 1.78, 9.97) and inversely with the birth of large-for-gestational-age newborns (OR: 0.19; 95% CI: 0.06, 0.62). No diet × genotype or exercise × genotype interaction was shown. Conclusion: The PNPLA3 SNP rs738409 G allele was associated with risk of mildly elevated transaminases in GD independent of a lifestyle intervention and despite a significant reduction in insulin resistance and risk of macrosomic offspring. This trial was registered at clinicaltrials.gov as NCT01506310.